Limits of the evidence initiative of the court of first instance and the reliable evidence procedure (Ius Novum, 2024)
This article aims to delineate the boundaries of the evidence initiative of the Court of the First Instance, which bears the responsibility to fulfil the goals of criminal proceedings, as outlined in Article 2 § 1 item 1 and § 2 of the Code of Criminal Procedure, from the perspective of evidence reliability, an essential component of the fair criminal trial concept. The court’s evidentiary actionswere thus examined through the lens of requirements stemming from Article 6(1) and (3) of the ECHR, especially the principles of independence, impartiality, adversarial process, immediacy, and access to criminal proceeding materials. The article adopts a dogmatic approach, building on an analysis of current national legal standards and the Rome Convention’s provisions, viewed through doctrine and jurisprudence of national courts and the Court in Strasbourg. This makes the publication relevant for both legal scholars and practitioners involved in criminal proceedings. The analysis suggests that the court’s initiative to introduce evidence, its methods of evidence gathering, and access to collected materials during proceedings must not curtail the rights of the parties, especially the accused, to conduct their evidentiary activities. Depriving the court of the primacy of independence and impartiality, restricting the parties’ capacity to engage in dispute in favour of an inquisitorial jurisdictional body violates the right to fair evidentiary proceedings. The court, in safeguarding the principle of material truth, must remember its role as a justice administrator and balance all arguments accordingly. Seeking evidence solely to establish the accused’s guilt contradicts the procedural function of adjudication and compromises the court’s neutrality, making it an extension of the prosecution. Hence, a thorough elucidation of case circumstances by the court should not disempower the parties, particularly regarding their initiative to present evidence.
Keywords: criminal proceedings, evidence initiative of the court, impartiality of the judge, reliable evidence proceedings, the accused